SAT0299 Apremilast: Pooled Safety Analysis of Three Phase 3, Randomized, Controlled Trials in patients with Psoriatic Arthritis. (23rd January 2014) - Mease, P. J.; Kavanaugh, A.; Adebajo, A. O.; Gomez-Reino, J. J.; Wollenhaupt, J.; Cutolo, M.; Schett, G.; Lespessailles, E.; Shah, K.; Hu, C.; Stevens, R.; Edwards, C. J.; et al.
Abstract : Background: Apremilast (APR), an oral small molecule specific inhibitor of phosphodiesterase 4, works intracellularly to modulate inflammatory mediators. The PALACE 1, 2 and 3 trials compared APR efficacy and safety vs placebo (PBO) in patients with active PsA despite prior DMARDs and/or biologics. Objectives: The overall safety and tolerability of APR was assessed in a pooled analysis of the PBO-controlled phases of PALACE 1, 2 and 3. Methods: Safety data was pooled from three phase 3, randomized, PBO-controlled, double-blind studies in which patients with active PsA inadequately controlled by DMARDs and/or biologics were randomized 1:1:1 to PBO, APR 20 mg BID, or APR 30 mg BID (stratified by baseline DMARD use). At wk 16, patients with <20% reduction in swollen and tender joint counts were required to be re-randomized to APR 20 mg BID or 30 mg BID (early escape) if first randomized to the PBO group or remained on initial APR dose. Patients continued treatment through wk 24. Stable concurrent DMARD therapy was allowed (MTX, sulfasalazine, leflunomide, or combination). The analysis comprises all data from the PBO-controlled periods (wks 0-≤24). Results: 1493 patients were randomized to PBO (n=495), APR 20 mg BID (n=501), or APR 30 mg BID (n=497) and included in the safety population. Baseline demographic and disease characteristics and prior and concurrent therapy were comparable across treatment groups; 22.4% had prior biologic exposure. Adverse events (AEs) occurred in 47.5% of patients receiving PBO, 61.5% of patients receiving APR 20 mg BID, and 60.8% of patients receiving APR 30 mg BID. AEs occurring in ≥5% of any treatment group were diarrhea, nausea, headache, and URTI (Table ). Of patients with these AEs, the majority (93-96%) were mild or moderate in severity and most were self-limited; discontinuation rates due to AEs were low (PBO, 4.2%; APR 20 mg BID, 5.6%; APR 30 mg BID, 7.2%). Serious AEs occurred in 3.8, 3.4, and 3.8% of PBO, APR 20 mg and APR 30 mg BID patients, respectively. One death occurred (APR 20 mg BID) due to multi-organ failure not suspected to be treatment-related. No cases of systemic opportunistic infections, lymphoma, vasculitis or reactivation/de novo TB were reported. There were no clinically meaningful differences between APR and PBO in terms of major adverse cardiovascular events, changes in blood pressure, malignancies, and clinically meaningful effects on laboratory measurements. Conclusions: APR was generally well tolerated with no new safety concerns identified compared with the known safety profile. Disclosure of Interest: P. Mease Grant/research support from: Abbvie, Amgen, BiofenIdec, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Glaxo SmithKline, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BiofenIdec, Bristol-Myers Squibb, Genentech, Janssen, Glaxo SmithKline, Lilly, Pfizer, UCB, A. Kavanaugh Grant/research support from: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene, Centocor-Janssen, Pfizer, Roche and UCB, A. Adebajo: None Declared, J. Gomez-Reino Grant/research support from: Roche and Schering-Plough, Consultant for: Bristol-Myers Squibb, Pfizer, Roche, Schering-Plough and UCB SA, Speakers bureau: Bristol-Myers Squibb, Roche, Schering-Plough and Wyeth, J. Wollenhaupt Consultant for: Abbott Laboratories, Bristol-Myers Squibb, MSD, Pfizer and UCB, M. Cutolo Grant/research support from: Actelion, BMS, Sanofi-Aventis, G. Schett Grant/research support from: Celgene, Consultant for: Abbott Laboratories, UCB, and Roche, E. Lespessailles Grant/research support from: Novartis, Lilly, Servier, Amgen, Speakers bureau: Novartis, Lilly, K. Shah Employee of: Celgene, C. Hu Employee of: Celgene, R. Stevens Employee of: Celgene, C. Edwards Grant/research support from: Pfizer, Consultant for: Samsung, Roche, Celgene, Speakers bureau: Roche, Pfizer, Abbott, GSK, C. Birbara Grant/research support from: Amgen, Lilly, Pfizer, Incyte, Merck, Bristol-Myers Squibb